PREVENTION OF ATRIAL FIBRILLATION - Juraev Umarkhon Ulugbek oglu (Web of Journals Publishing, 2025)
Atrial fibrillation is one of the most common heart rhythm disorders, associated with a high risk of stroke, heart failure, and mortality. This article reviews the key pathophysiological mechanisms of atrial fibrillation development, risk factors, clinical manifestations, and consequences of arrhythmia. Particular attention is paid to modern prevention strategies, including primary prevention in patients at risk and secondary prevention in individuals with established disease. Recommendations for monitoring blood pressure, body weight, managing concomitant diseases, and approaches to antiarrhythmic and anticoagulant therapy are presented. The role of catheter ablation and cardiac rehabilitation in reducing relapses and improving the quality of life of patients.
Keywords: Atrial fibrillation; arrhythmia; prevention; stroke; anticoagulants; antiarrhythmics ; catheter ablation ; cardiology.